A systematic review and meta-analysis of pathogen reduction in onsite sanitation systems - Isaac G. Musaazi; Shane McLoughlin; Heather M. Murphy; Joan B. Rose; Nynke Hofstra; Innocent K. Tumwebaze; Matthew E. Verbyla (Water Research X, 2023)
The safe management of fecal sludge from the 3.4 billion people worldwide that use onsite sanitation systems can greatly reduce the global infectious disease burden. However, there is limited knowledge about the role of design, operational, and environmental factors on pathogen survival in pit latrines, urine diverting desiccation toilets, and other types of onsite toilets. We conducted a systematic literature review and meta-analysis to characterize pathogen reduction rates in fecal sludge, feces, and human excreta with respect to pH, temperature, moisture content, and the use of additives for desiccation, alkalinization, or disinfection. A meta-analysis of 1,382 data points extracted from 243 experiments described in 26 articles revealed significant differences between the decay rates and T99 values of pathogens and indicators from different microbial groups. The overall median T99 values were 4.8 days, 29 days, >341 days, and 429 days for bacteria, viruses, protozoan (oo)cysts, and Ascaris eggs, respectively. As expected, higher pH values, higher temperatures, and the application of lime all significantly predicted greater pathogen reduction rates but the use of lime by itself was more effective for bacteria and viruses than for Ascaris eggs, unless urea was also added. In multiple lab-scale experiments, the application of urea with enough lime or ash to reach a pH of 10 – 12 and a sustained concentration of 2,000 – 6,000 mg/L of non-protonated NH3N reduced Ascaris eggs more rapidly than without urea. In general, the storage of fecal sludge for 6 months adequately controls hazards from viruses and bacteria, but much longer storage times or alkaline treatment with urea and low moisture or heat is needed to control hazards from protozoa and helminths. More research is needed to demonstrate the efficacy of lime, ash, and urea in the field. More studies of protozoan pathogens are also needed, as very few qualifying experiments were found for this group.